The Impact of Government Infrastructure Spending on Economic Growth and Poverty in Gorontalo Province - Destin Fauzia Sahi; Muhammad Amir Arham; Ivan R Santoso (Jambura Equilibrium Journal, 2020)
This research aims to analyse the impact of government infrastructure spending on economic growth and poverty in Gorontalo Province. This research uses datasets on government expenditure, economic growth, and poverty rate from Central Statistics Bureau (Badan Pusat Statistik, BPS), Directorate General of Fiscal Balances Ministry of Finance. This research uses panel data regression in 5 regencies during 2013-2017 in Gorontalo Province. The main results of this research show that (i) public works has negative and insignificant impact on economic growth; (ii) the public housing sector has a negative and not significant impact on economic growth; (iii) the transportation sector has a positive and insignificant impact on economic growth; (iv) the public works sector has a negative and not significant impact on poverty; (v) the public housing sector has a positive and insignificant impact on poverty; (vi) the transportation sector has a negative and not significant impact on poverty. Keywords: Economic Growth; Poverty; Infrastructure; Government Spending.